Cooperate to play: How in-game cooperation knowledge impacts online gamer loyalty. (June 2023) - Linh Pham, Thi Tuan; Huang, Tzu-Ling; Liao, Gen-Yih; Chou, Yu-Jen; Cheng, T.C.E.; Teng, Ching-I
Abstract: Online games are prominent computer applications worldwide. Gamers form teams to cooperate to achieve gaming goals. If gamers do not have in-game cooperation knowledge, they may find it difficult to integrate into gaming groups (e.g., teams and communities), which may further undermine their loyalty toward online games. Nevertheless, little is known about how in-game cooperation knowledge forms online gamer loyalty, indicating a research gap. This gap hinders game makers from effectively allocating resources to strengthen gamer loyalty. Based on social capital theory, we develop a model to fill this gap. We collected 3036 responses from online gamers and used hierarchical regression to analyze the data. We find that cooperation knowledge, team participation experience, and gaming community identification are positively related to online gamer loyalty. Moreover, cooperation knowledge strengthens the relationship between team participation experience and loyalty. Overall, our findings uniquely inform game providers that gamers' cooperation knowledge not only directly strengthens gamer loyalty but also amplifies the positive impact of team participation experience on loyalty. Highlights: We examine how in-game cooperation knowledge formulates gamer loyalty. Such knowledge, team participation, and community identification fuel loyalty. Such knowledge strengthens the link from team participation to gamer loyalty.